Proceedings of the 16th Annual Joint Conference on Innovation and Technology in Computer Science Education 2011
DOI: 10.1145/1999747.1999796
|View full text |Cite
|
Sign up to set email alerts
|

Habits of programming in scratch

Abstract: Visual programming environments are widely used to introduce young people to computer science and programming; in particular, they encourage learning by exploration. During our research on teaching and learning computer science concepts with Scratch, we discovered that Scratch engenders certain habits of programming: (a) a totally bottom-up development process that starts with the individual Scratch blocks, and (b) a tendency to extremely fine-grained programming. Both these behaviors are at odds with accepted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(79 citation statements)
references
References 9 publications
1
71
0
2
Order By: Relevance
“…Because Tiled Grace enforced scoping of variable-reference tiles (necessary, as the textual language has traditional lexical scoping, and in fact intended to help by offering a list of available names), assembling code in this way was sometimes not possible, to the frustration of the user. One of the trade-offs in integrating the textual and block languages that we had not considered was that this sort of "inside-out" construction, which is very natural and widely-reported [53] in block languages, would be stymied by error prevention in the textual language. Meerbaum-Salant et al have argued that this style is in fact a "bad habit" [53], and that it has a longer-term detrimental effect on learners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Tiled Grace enforced scoping of variable-reference tiles (necessary, as the textual language has traditional lexical scoping, and in fact intended to help by offering a list of available names), assembling code in this way was sometimes not possible, to the frustration of the user. One of the trade-offs in integrating the textual and block languages that we had not considered was that this sort of "inside-out" construction, which is very natural and widely-reported [53] in block languages, would be stymied by error prevention in the textual language. Meerbaum-Salant et al have argued that this style is in fact a "bad habit" [53], and that it has a longer-term detrimental effect on learners.…”
Section: Discussionmentioning
confidence: 99%
“…One of the trade-offs in integrating the textual and block languages that we had not considered was that this sort of "inside-out" construction, which is very natural and widely-reported [53] in block languages, would be stymied by error prevention in the textual language. Meerbaum-Salant et al have argued that this style is in fact a "bad habit" [53], and that it has a longer-term detrimental effect on learners. It is not obvious whether this aspect of Tiled Grace is helping or hindering, and precisely what the long-term goals are may again be important.…”
Section: Discussionmentioning
confidence: 99%
“…Modkit has been used in workshops teaching children how to program Arduino [17]. Yet while Scratch has been studied to some extent, so far there are no similar studies to investigate the benefits of ModKit or other VPLs for the Arduino. There are also some concerns about the habits Scratch engenders [15]. Following a constructivist philosophy of learning-by-making, Scratch both supports and encourages a bottom-up approach to program construction -programming by bricolage [19], rather than design.…”
Section: Related Workmentioning
confidence: 99%
“…In "Habits of Programming in Scratch," Meerbaum-Salant, et al [46] found that while Scratch encourages self-directed learning, students only really learned programming concepts when explicitly taught them. The habits they found in novice programmers learning with Scratch include bottom-up programming and extremely fine-grained programming.…”
Section: Scratchmentioning
confidence: 99%
“…Multiple studies have been performed investigating the effectiveness of Scratch in teaching introductory programming concepts [44,46,47,49,53,54]. It works well for some concepts (loops and conditionals) but not for others (variables and functions) [49].…”
Section: Platform Choicementioning
confidence: 99%